Understanding the Role of Objects in Cross-Disciplinary Collaboration - Nicolini, Davide; Mengis, Jeanne; Swan, Jacky (Organization Science, 2012)
In this paper we make a case for the use of multiple theoretical perspectives—theory on boundary objects, epistemic objects, cultural historical activity theory, and objects as infrastructure—to understand the role of objects in cross-disciplinary collaboration. A pluralist approach highlights that objects perform at least three types of work in this context: they motivate collaboration, they allow participants to work across different types of boundaries, and they constitute the fundamental infrastructure of the activity. Building on the results of an empirical study, we illustrate the insights that each theoretical lens affords into practices of collaboration and develop a novel analytical framework that organizes objects according to the active work they perform. Our framework can help shed new light on the phenomenon, especially with regard to the shifting status of objects and sources of conflict (and change) in collaboration. After discussing these novel insights, we outline directions for future research stemming from a pluralist approach. We conclude by noting the managerial implications of our findings.